Analysis of Medicinal Chemicals Contained on Jamu: A Review - Syahfitr, Sari Anggraini; Asra, Dan Ridho (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Jamu is commonly known as an Indonesian traditional herbal medicine that contains ingredients or ingredients derived from plants, animals, minerals, galenic, or mixtures of these ingredients that have been hereditary for medicinal use. Some studies reported the presence of medicinal chemicals that are deliberately added to Jamu. Jamuthat containing medicinal chemicals usually had a faster healing effect compared to Jamu that do not contain medicinal chemicals. Jamu added medicinal chemicals cause serious side effects if it is consumed regularly, overdose, and long period consumption with uncontrolled dosage or its interaction with other substances on jamu formulation. Purpose: This review article aims to summarize several methods used to analyze medicinal chemicals contained in jamu. Data source:The author created thisreview article by conducting literature studies. The literature was collected from national and international journals published in the last ten years (2010-2020). The works of literature were collected from trusted online journal sites such as the digital library, Google, Google scholar/Google Cendekia, PubMed, ScienceDirect, NCBI, Researchgate, and other E-resource with the keyword “Jamu”, “medicinal chemicals”, and “analysis of medicinal chemicals”. Conclusion: Jamu products that containing medicinal chemicals are jamu pegal linu, weight loss, stamina enhancer, diabetes, antihypertensive and dietary supplements. The medicinal chemicals used are sodium diclofenac, paracetamol, piroxicam, ibuprofen, dexamethasone, mefenamic acid, phenolphthalein, sibutramine, fenfluramine, sildenafil, tadalafil, thiosildenafil, caffeine, ephedrine, nifedipine, glibenclamide. Herbal Medicine was analyzed by the TLC method (thin layer chromatography), Densitometry-chromatography, thin-layer chromatography-Spectrophotometry, SERS-thin layer chromatography, Spectrophotometry, HPLC (High-Performance Liquid Chromatography), HPLC-ESI-MS/MS (high-performance liquid. chromatography/electrospray ionization tandem mass spectrometry), HPLC-Densitometry (High-Performance Liquid Chromatography-densitometry), UHPLC-Q-ORTIP HERMS (ultra-high-performance liquid chromatography-Quadrupole-orbitrap high-resolution mass spectrometry), UPLC/Q-TOF MS (ultra-performance liquid chromatography (UPLC) coupled with quadrupole-time-of-flight mass spectrometry (Q-TOF MS), Capillary electrophoresis (CE), GC-MS (Gas Chromatography-Mass Spectrometry), LC-MS (Liquid Crhomatogaph Mass) Spectrometry), Prototype Test-Strip, Infrared spectroscopy.